2023
DOI: 10.3389/fcell.2023.1115229
|View full text |Cite
|
Sign up to set email alerts
|

Early-life exposure to di (2-ethyl-hexyl) phthalate: Role in children with endocrine disorders

Abstract: Di (2-ethyl-hexyl) phthalate (DEHP), one of endocrine-disrupting chemicals (EDCs), has widespread concern due to its serious health hazards. Exposure to DEHP in the early stage of life affects fetal metabolic and endocrine function, which even would cause genetic lesions. To date, it is widely believed that the increasing incidence of childhood obesity and diabetes in adolescents is related to the impact of DEHP on glucose and lipid homeostasis in children. However, there remains a knowledge gap to recognize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Women employed in the medical field, manufacturing, or agricultural sector may be exposed to elevated concentrations of endocrine-disrupting chemicals including diethylhexyl phthalate (DEHP), which could provide a significant risk of toxicity to their fetus when exposure occurs during pregnancy (Bonde, 2020). DEHP is a phthalate derivative used in various aspects of daily life, including cosmetics, clothing, toys, household items, food packaging, and medical supplies (Zeng et al, 2023). Studies have shown that DEHP can pass from the mother to the fetus through the placenta and can directly or indirectly affect the 1 fetus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women employed in the medical field, manufacturing, or agricultural sector may be exposed to elevated concentrations of endocrine-disrupting chemicals including diethylhexyl phthalate (DEHP), which could provide a significant risk of toxicity to their fetus when exposure occurs during pregnancy (Bonde, 2020). DEHP is a phthalate derivative used in various aspects of daily life, including cosmetics, clothing, toys, household items, food packaging, and medical supplies (Zeng et al, 2023). Studies have shown that DEHP can pass from the mother to the fetus through the placenta and can directly or indirectly affect the 1 fetus.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that DEHP can pass from the mother to the fetus through the placenta and can directly or indirectly affect the 1 fetus. Accordingly, intrauterine DEHP exposure may lead to errors in gene coding and expression, causing postnatal and adulthood energy metabolism disruptions and endocrine disorders (Zeng et al, 2023).…”
Section: Introductionmentioning
confidence: 99%